2011
DOI: 10.4149/neo_2011_01_51
|View full text |Cite
|
Sign up to set email alerts
|

Fine-needle aspiration biopsy of cervical lymph nodes: factors in predicting malignant diagnosis

Abstract: The objective of the study was to determine the predicting factors in malignant diagnosis in ultrasonography guided fine-needle aspiration biopsy of cervical lymph nodes. Design is retrospective follow-up study. Ultrasonography guided fine-needle aspiration biopsies of cervical lymph nodes were performed in 290 patients. The mean age was 45.5 ± 14.4 years (range; 15-85). 207 (71.4%) and 83 (28.6%) were women and men, respectively. Cytopathologist was not present in any biopsy procedure. Factors in predicting m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…It is reported that the nondiagnostic rate of FNA is higher at level VI than at lateral compartment in patients who had received surgery of the central neck. 28,29 In this scenario, it is suggested to repeat biopsy of the central nodes until an unequivocal diagnosis is made. 28,29 Certain limitations of this study should be noted.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is reported that the nondiagnostic rate of FNA is higher at level VI than at lateral compartment in patients who had received surgery of the central neck. 28,29 In this scenario, it is suggested to repeat biopsy of the central nodes until an unequivocal diagnosis is made. 28,29 Certain limitations of this study should be noted.…”
Section: Resultsmentioning
confidence: 99%
“…28,29 In this scenario, it is suggested to repeat biopsy of the central nodes until an unequivocal diagnosis is made. 28,29 Certain limitations of this study should be noted. First, it may be subjected to selection bias because only those patients who had received US and USgFNA were included.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When combined with the detection of NONHSAT076754, the diagnostic value of ultrasonography was also greatly increased for the differentiation of PTC with LNM from PTC without LNM. Ultrasonography is a useful tool for the identification and location of metastasis in the neck; however, for lymph nodes without typical signs of metastasis (e.g., microcalcification, cystic changes) [32], it is difficult to make a decision regarding surgery through ultrasonography alone. NONHSAT076754 is of great value for the indication of the existence of LNM in PTC.…”
Section: Discussionmentioning
confidence: 99%
“…US‐guided fine‐needle aspiration (USFNA) is an easy, safe, and cost‐effective technique for diagnosing malignant lymph nodes in the head and neck with a variable range of diagnostic accuracy from 79% to 94.5% . Studies comparing USFNA and US‐guided core‐needle biopsy (USCNB) have reported that the diagnostic performance of USCNB is superior or comparable to that of USFNA in different regions in the body .…”
Section: Introductionmentioning
confidence: 99%